Carotid Intima–Media Thickness May Be a Useful Biomarker in Determining Early Cardiovascular Risk in Mild Autonomic Cortisol Hypersecretion - Demir, Ahmet Numan; Durcan, Emre; Mefkure Özkaya, Hande; Haliloğlu, Özlem; Keskin, Fatma Ela; Kadıoğlu, Pınar (Cerrahpaşa Medical Journal, 2024)
Objective: This study aimed to assess the cardiovascular risk in patients with mild autonomous cortisol hypersecretion (MACS). To this end, the suitability of carotid intima–media thickness (cIMT) as a surrogate biomarker was evaluated. Methods: This cross-sectional study was conducted with patients presenting to the endocrinology outpatient clinic of a tertiary care hospital. Patients with adrenal Cushing’s syndrome (CS), MACS and nonfunctional adrenal adenoma (NFA) were consecutively included. Patients with known cardiovascular disease were excluded. Biochemical data and sonographically determined cIMT values were collected. Data were compared between the three groups. Results: A total of 20 CS patients with a mean age of 49.3 ± 6.9 years, 19 MACS patients with a mean age of 48.1 ± 11.1 years, and 19 NFA patients with a mean age of 41.7 ± 13.3 years were included in this study (P = .158). Cushing’s syndrome and MACS patients had significantly higher mean cIMT values compared to NFA patients (P < .001 and P = .0048, respectively). However, when patients with diabetes and obesity were excluded, cIMT did not differ between MACS and NFA patients (P = .861). Nevertheless, it was still significantly higher in CS patients compared to MACS and NFA patients (P = .005 and P = .002, respectively). Conclusion: This study confirms the presence of vascular damage and increased cardiovascular risk in patients with CS. We also found vascular damage in patients with MACS. Carotid intima–media thickness could be a useful biomarker for early assessment of cardiovascular risk in patients with MACS. Cite this article as: Demir AN, Durcan E, Özkaya HM, Haliloğlu Ö, Keskin FE, Kadıoğlu P. Carotid intima–media thickness may be a useful biomarker in determining early cardiovascular risk in mild autonomic cortisol hypersecretion. Cerrahpaşa Med J. 2024;48(2):119-124.